Student-designed inquiry effects on scientific reasoning and conceptual understanding in physics - Taduran, Regina Carla R.; Monterola, Sheryl Lyn C. (2016)
Access online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/5787
Keywords: Concept learning; Reasoning; Physics education (Secondary)